The development of public relation skills in aspiring community college presidents - Van Houten, Peter, author; Kuk, Linda, advisor; Davies, Tim, advisor; Anderson, Sharon, committee member; Hallahan, Kirk, committee member (Colorado State University. Libraries, 2014)
Numerous studies warn community colleges about a growing shortage of available presidents in the coming decade (Duree, 2007). The American Council on Education pointed to this problem in a 2012 American College President Study that found 51 percent of presidents in 2011 were 61 to 70 years old, up from 37 percent only five years prior. Eddy (2012) noted this high number of older presidents and said their pending retirements should serve notice to community colleges that they need to work harder to develop new campus leaders. Within my qualitative study, I looked at the preparation of leaders through the experiences of current community college vice presidents who someday want to be a president. Taking a phenomenological approach, I interviewed 11 vice presidents working in several states west of the Mississippi River. I wanted to know more about what the vice presidents were doing to prepare themselves for a presidency, especially related to the community college president's public relations role. The literature indicated today's community college presidents are expected to have a larger role in the community and form strong partnerships with business leaders, donors, media outlets, and legislators (Cook, 2012). I was interested to see if they felt they were ready for that role, as well as what leadership development tools helped them grow as administrators and future presidents. Surprisingly, we spent a large portion of our interviews discussing impediments to their development and the challenges they faced as they advanced in their respective careers. From my findings, I learned that the vice presidents are struggling with their development efforts because of time limitations and a chaotic environment within many campuses. In addition to a lack of time and financial resources, many of the vice presidents indicated that much of their development efforts have been done on their own. Some of the vice presidents said they were comfortable with the public relations role and have experienced some training in that arena, either in actual practice, observation or coursework. Others indicated less comfort with the public relations expectations or a feeling that this role is overrated or overvalued. The most effective developmental tools for public relations appeared to be current presidents. Impediments in leadership growth also fell on some presidents who were not willing to allow their vice presidents a chance to experience public relations roles.
Keywords: leadership; community college; community relations; leadership development; presidents; public relations